Pattern of diseases among visitors to Mina health centers during the Hajj season, 1429 H (2008 G) - Abdullah G. Alzahrani; Abdul Jamil Choudhry; Mohammad A. Al Mazroa; Abdul Hafiz M. Turkistani; Ghassan S. Nouman; Ziad A. Memish (Elsevier, 2012)
Background: While performing the Hajj, hajjis face different risks related to the environment, their behaviors and their health conditions that can result in a variety of diseases. The objective of this study was to determine the pattern of diseases among pilgrims seeking medical services in Mina primary health care centers (PHCCs) during the Hajj season in 1429 (2008). Methods: This is a descriptive study based on the medical records of a random sample of 4136 patients who attended 13 randomly selected Mina PHCCs from 8 to 12 Dhu-Alhijja, 1429 H (6-10 December 2008). Results: The majority of the patients were men (70.7%), and most of the patients were between 45 and 64 years of age (42.8%). One-fifth (20.2%) of the patients suffered from multiple diseases. Respiratory diseases were the most common (60.8%), followed by musculoskeletal (17.6%), skin (15.0%) and gastrointestinal (13.1%) diseases. Diabetes, asthma and hypertension each constituted less than 3% of the total diseases. Respiratory diseases were the most common independent of nationality or the day of visit, while the frequency of the other diseases varied according to nationality and the day of visit. The most frequently prescribed drugs were analgesics, antipyretics, antibiotics and cough syrups. Conclusion: This study describes the pattern of diseases among pilgrims attending Mina PHCCs, which may aid in providing the best possible health care services to pilgrims. Keywords: Hajj, Saudi Arabia, Disease pattern, Primary health centers